Factors That Can Affect the Occurrence Urinary Stone - Mohammad Miftachul Ulum; Mujito; Imam Sunarno (JOSAR (Journal of Students Academic Research), 2022)
Urinary tract stones are the biggest health problem in the field of urology with typical symptoms of pain that can lead to complications in the kidneys. The formation of the stones in the urinary tract (kidneys, ureters, and uretra) due to the deposition of substances in abnormal amounts caused by internal and external factors. The purpose of this study was to determine the factors that can influence the occurrence of Urinary Tract Stones. This study uses a literature review. The Literature Review search uses a database with Google Scholar and keywords that are adjusted to the Medical Subject Heading (MeSH). Data analysis used quality analysis methodology with checklists. The results showed the factors that influence the occurrence of urinary tract stones, among others; heredity, age, gender (male), obesity (BMI> 25) and behavior (regulation of fluid intake <1500 ml per day, diet (consumption of high oxalate vegetables), and length of time to sit. Education to the public through health services regarding the factors that can affect the incidence of urinary tract stones needs to be implemented. Keywords: Factors, Urinary Tract Stones Urinary tract stones are the biggest health problem in the field of urology with typical symptoms of pain that can lead to complications in the kidneys. The formation of the stones in the urinary tract (kidneys, ureters, and uretra) due to the deposition of substances in abnormal amounts caused by internal and external factors. The purpose of this study was to determine the factors that can influence the occurrence of Urinary Tract Stones. This study uses a literature review. The Literature Review search uses a database with Google Scholar and keywords that are adjusted to the Medical Subject Heading (MeSH). Data analysis used quality analysis methodology with checklists. The results showed the factors that influence the occurrence of urinary tract stones, among others; heredity, age, gender (male), obesity (BMI> 25) and behavior (regulation of fluid intake <1500 ml per day, diet (consumption of high oxalate vegetables), and length of time to sit. Education to the public through health services regarding the factors that can affect the incidence of urinary tract stones needs to be implemented. Keywords: Factors, Urinary Tract Stones